Rancang Bangun Pembangkit Listrik Tenaga Surya dan Kendali Pakan Otomatis Berbasis ESP32 - Prasetyo Dwi Putro; Ayusta Lukita Wardani (Politeknik Negeri Malang, 2024)
One fundamental energy needed for many aspects of daily living is electricity. Most commonly known application of electricity is in the Megaluh Village lobster pond. Due to the fact that air is essential to lobster life, an aerator must be used. Due to the distance between the farmer's residence and other issues, the aerator needs to be operated every 24 hours. The goal of this project is to build an automatic feeder based on ESP32 and a solar plant as a substitute energy source. The experiment's findings indicate that on day two, the solar panel reached its maximum efficiency of 55,74W. On the fifth day, though, the average daily was only around 41,07 W. In relation to the battery life indicator, it is around 12,72V and 2,96A. Furthermore, the battery's output voltage on the last day was 12.03 V and its resistance was 2,64A. Additionally, the average for the inverter's output over five days is 230,5V and 0.13A. The results of the optimal angle servo were 47° because provided according to the required weight, which was 10 grammes. When using a digital timing device, a load cell can achieve a 99% accuracy rate.